Research on lung tumor image segmentation algorithm based on U⁃Net; Молодежь и современные информационные технологии - Ван Юйцянь (2025, 2025)
Aiming at the problem of complex and variable tumor regions and fuzzy boundaries in lung CT images, an improved U⁃Net network is proposed by introducing the attention mechanism and optimizing the loss function. Training is performed on a clinical multimodal medical dataset to verify the effectiveness of the algorithm